A genetic evaluation of growth, ultrasound, and carcass traits at alternative slaughter endpoints in crossbred heavy lambs. (30th November 2018) - Massender, Erin; Brito, Luiz F; Cánovas, Angela; Baes, Christine F; Kennedy, Delma; Schenkel, Flavio S
Abstract: Genetic parameters were estimated for growth, ultrasound, and carcass traits in a Canadian crossbred heavy lamb population. Traits analyzed included birth, weaning, post-weaning, and ultrasound scanning weights; pre- and post-weaning average daily gain; ultrasonically measured eye muscle and fat depths; hot carcass weight; fat depth at the GR site (110 mm from the midline on the 12th rib); carcass conformation scores; saleable meat yield; price grid value; and total carcass value. The impact of three alternative slaughter endpoints (slaughter age, carcass weight, and carcass fatness) on genetic parameter estimates was also evaluated. In general, carcass traits were found to be moderately heritable, with heritability estimates ranging from 0.17 ± 0.02 for hot carcass weight at a constant slaughter age to 0.34 ± 0.02 for average carcass conformation score at a constant carcass weight. Heritability estimates were similar when observations were adjusted to alternative slaughter endpoints, but for some traits, phenotypic variance and genetic correlation estimates differed. Genetic correlations between carcass traits and growth and ultrasound traits were typically favorable. Ultrasonically measured eye muscle depth and fat depth were found to be moderately to strongly positively correlated with hot carcass weight (0.33 ± 0.15 to 0.71 ± 0.19) and fat depth at the GR site (0.38 ± 0.14 to 0.74 ± 0.12), respectively, reaffirming the usefulness of selection on ultrasound traits to improve carcass yield and quality. Genetic correlations among carcass traits were generally favorable, with the exception of moderate unfavorable positive genetic correlations between fat depth at the GR site and primal cut carcass conformation scores (0.31 ± 0.05 to 0.60 ± 0.05). Overall, the results of this research suggest that there is potential to improve carcass yield and quality through genetic selection and provides the population-specific genetic parameter estimates needed for the genetic evaluation of carcass traits in the Canadian sheep population. Nevertheless, the optimal endpoint for carcass trait genetic evaluations will need to be further investigated, considering both the current findings and additional information on production practices in the industry.